(untitled) (Homoeopathy for All, 2024)
Homoeopathy is one of the oldest originated complementary and alternative medicine which was introduced in Europe more than 200 years ago. Homoeopathy was first introduced in India by the Germans in the year 1810 and it started becoming popular in the year 1839. The demand of homoeopathic remedies is on an unprecedented rise which has attracted the attention of the general masses. The Government of India is serious about the quality of homoeopathic education, research in homoeopathy, quality of homoeopathic medicines and its proper regulation for manufacturing and sale.